Assessing AODV Protocol Suitability for Collision Avoidance Systems - Kanani, Pratik; Saini, Jatinderkumar R.; Sankhe, Darshana; Patil, Deepali; Pandya, Gayatry; Nanade, Archana; Shah, Bhoomi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In Vehicular Ad-hoc Networks (VANETs), the communication is not limited to message transmission but also encompasses the dissemination of crucial information to avert catastrophic incidents. This message exchange occurs through diverse routing protocols, which comprise a predefined set of instructions for both vehicles on the road and stationary vehicles, serving as intermediaries to forward messages to vehicles ahead, known as road-side units (RSU). In this research, our primary focus revolves around the examination and comprehension of the AODV model, recognized for its effectiveness in handling variations in vehicle speed, vehicle density, and average throughput, outperforming other protocols. Specifically, our investigation delves into the performance of the AODV protocol in scenarios where multiple nodes coexist in close proximity, particularly in delivering collision avoidance messages. In high-density vehicular environments, the AODV protocol faces challenges such as broadcast storms and limited link lifetimes, which hinder the successful transmission of collision messages. This paper scrutinizes and translates these phenomena into a mathematical model for further analysis. The traditional AODV protocol demonstrates diminished efficiency in situations where nodes are unreachable, forwarding paths become unstable, link lifetimes are brief, and broadcast storms occur.